PERCERAIAN SECARA KHUL’: PERUNTUKAN SERTA PELAKSANAANNYA MENURUT ENAKMEN UNDANG-UNDANG KELUARGA ISLAM NEGERI JOHOR (KAJIAN KES 1995-1997) - Nasohah, Zaini (Jurnal Syariah, 2019)
Each and every one of a husband and wife in such a marriage hopes that they can live together in harmony. However, there are ways out for coupLes if they have troubLesome with their marriage i.e divorce or separate. What is commonLy practised in Muslim society that separation or divorce is inevitabLe, a husband will divorce his wife. Instead, this article attempts Â·to eLobarate in some details another type of divorce known as aL-KhuL’, or in MaLay as "tebus taLak". It is aLso discusses views of different madhiihib on the validity of khul ’ as well as provides some provisions on the subject in Muslim Family Law Enactment of lohor with some observation cases reported.